2004
DOI: 10.1074/jbc.m410967200
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic Actions of the Platelet-activating Factor Acetylhydrolase I α2 Catalytic Subunit

Abstract: Platelet-activating factor (PAF) is an important mediator of cell loss following diverse pathophysiological challenges, but the manner in which PAF transduces death is not clear. Both PAF receptor-dependent and -independent pathways are implicated. In this study, we show that extracellular PAF can be internalized through PAF receptor-independent mechanisms and can initiate caspase-3-dependent apoptosis when cytosolic concentrations are elevated by ϳ15 pM/cell for 60 min. Reducing cytosolic PAF to less than 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 47 publications
2
49
0
Order By: Relevance
“…Cytosolic PAF-AH Ib is an acetylhydrolasespecific complex composed of two 29-kDa ␣ 1 and/or 30-kDa ␣ 2 catalytic subunits and two 45-kDa regulatory LIS1 subunits (15). We have previously shown that overexpression of the ␣ 2 catalytic subunit enhances PAF hydrolysis in cells that endogenously express all three PAF-AH Ib subunits (16). As observed over the course of CNS development (17), the ␣ 1 catalytic subunit was detected at higher levels before differentiation, while the ␣ 2 catalytic and LIS1 regulatory subunits were maximally expressed following terminal differentiation of hNT neurons (Fig.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Cytosolic PAF-AH Ib is an acetylhydrolasespecific complex composed of two 29-kDa ␣ 1 and/or 30-kDa ␣ 2 catalytic subunits and two 45-kDa regulatory LIS1 subunits (15). We have previously shown that overexpression of the ␣ 2 catalytic subunit enhances PAF hydrolysis in cells that endogenously express all three PAF-AH Ib subunits (16). As observed over the course of CNS development (17), the ␣ 1 catalytic subunit was detected at higher levels before differentiation, while the ␣ 2 catalytic and LIS1 regulatory subunits were maximally expressed following terminal differentiation of hNT neurons (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…To test this directly, we used a biochemical loading approach to elevate intraneuronal C16:0 PAF concentrations in the absence of any other toxic stimuli. PAFs can be internalized following binding to PAFR and clatherin-mediated endocytosis, transglutaminase-dependent transmembrane bilayer movement, engagement with low affinity binding sites at the plasma membrane, or direct physicochemical effects at the plasma membrane (16,18,19). As hNT neurons do not express PAFR (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that Paf-ah-Ib's activity in spermatogenesis, apoptosis, and neuronal migration may not rest entirely in its catalytic ability to reduce PAF levels but that it may act as a signaling complex in conjunction with other proteins (4,5,14). The Alpha-2 isoforms described herein may introduce levels of regulation and interaction beyond Pafah1b2's catalytic activity imparting additional, as yet uncharacterized, links to intracellular signaling pathways in testis and other tissues.…”
Section: A Testis Specific Splice Variantmentioning
confidence: 92%
“…Binding of PAF to surface receptors activates intracellular second messenger signaling cascades, including protein kinase C, tyrosine kinases, and mitogen-activated protein kinases (MAPKs), depending on target cell type (2,3). PAF's actions are not limited to receptor interactions at the cell surface, as it is internalized either bound to receptors or via an as yet uncharacterized non receptor mediated pathway (4,5). Intracellular binding sites for PAF have been found in brain microsomal fractions (6) including a high affinity binding site implicated in transcriptional regulation (7).…”
Section: Introductionmentioning
confidence: 99%